2005
DOI: 10.1111/j.1523-1755.2005.00675.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of renin-angiotensin system blockade on renal angiotensin-(1-7) forming enzymes and receptors

Abstract: Our data revealed a role for ACE2 in Ang-(1-7) formation from Ang II in the kidney of normotensive rats as primarily reflected by the increased ACE2 activity measured in renal membranes from the kidney of rats given either lisinopril or losartan. The data further indicate that increased levels of Ang-(1-7) in the urine of animals after ACE inhibition or AT(1) receptor blockade reflect an intrarenal formation of the heptapeptide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

24
237
4
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 242 publications
(266 citation statements)
references
References 35 publications
(58 reference statements)
24
237
4
1
Order By: Relevance
“…This possibility was explored by our recent experiments in which ACE2 gene expression and activity was measured in the renal cortex of rats submitted to the same treatment protocols described above ( Figure 2C and 2D). 49 In these studies, renal cortex ACE2 mRNA was not changed by 12-day administration of lisinopril, losartan, or both drugs combined, although ACE2 activity was significantly increased by either treatment alone. 49 The demonstration of a tissue-specific regulation of ACE2 gene expression and ACE2 enzyme activity is additionally underscored by our finding of a differential effect of AT 1 receptor blockade on ACE2 mRNA in the aorta and carotid arteries of SHR.…”
Section: Ace2 and Ang-(1-7)mentioning
confidence: 81%
See 1 more Smart Citation
“…This possibility was explored by our recent experiments in which ACE2 gene expression and activity was measured in the renal cortex of rats submitted to the same treatment protocols described above ( Figure 2C and 2D). 49 In these studies, renal cortex ACE2 mRNA was not changed by 12-day administration of lisinopril, losartan, or both drugs combined, although ACE2 activity was significantly increased by either treatment alone. 49 The demonstration of a tissue-specific regulation of ACE2 gene expression and ACE2 enzyme activity is additionally underscored by our finding of a differential effect of AT 1 receptor blockade on ACE2 mRNA in the aorta and carotid arteries of SHR.…”
Section: Ace2 and Ang-(1-7)mentioning
confidence: 81%
“…49 In these studies, renal cortex ACE2 mRNA was not changed by 12-day administration of lisinopril, losartan, or both drugs combined, although ACE2 activity was significantly increased by either treatment alone. 49 The demonstration of a tissue-specific regulation of ACE2 gene expression and ACE2 enzyme activity is additionally underscored by our finding of a differential effect of AT 1 receptor blockade on ACE2 mRNA in the aorta and carotid arteries of SHR. In this study, we showed increased ACE2 gene expression in the aorta but not the carotid arteries of SHRs given olmesartan for 2 weeks.…”
Section: Ace2 and Ang-(1-7)mentioning
confidence: 81%
“…Imidapril increased the expression of renin mRNA probably through a negative feedback mechanism; however, it did not change the level of ANG, ACE or AT1-R mRNA, which is consistent with the results of an earlier report. 35 Fasudil did not affect the expression of ANG, renin or ACE mRNA, but slightly decreased that of AT1-R mRNA. We earlier reported that fasudil improved renal impairment in a salt-induced hypertensive rat model without changing plasma renin activity.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between ACE and ACE2 is demonstrated by the observation that ACE inhibition results in elevation of Ang 1-7 in vivo and blockade of Ang 1-7 with a specific antagonist reverses the antihypertensive effects of lisinopril. 4,6,18 Furthermore, a recent study demonstrated that lentiviral delivery of ACE2 can reverse cardiac hypertrophy in rats, suggesting not only that ACE2 is beneficial, but that manipulation of ACE2 may have therapeutic potential. 19 Direct evidence for ACE2 in the development of hypertensive cardiopathy and kidney disease comes from the ACE2 gene knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…4 Further, in rats treated with ACE inhibitors and angiotensin receptor blockers, an increase in local renal ACE2 activity is noted. 5,6 We have shown earlier that ACE is up-regulated in human diabetic nephropathy accompanied with hypertension, a condition associated with high Ang II levels. 7 Taken together, these findings suggest that there may be an alteration in the ACE/ACE2 balance in hypertension in a manner that favors increased Ang II generation (ie, upregulation of ACE) and decreased Ang II degradation (ie, down-regulation of ACE2) during hypertension.…”
mentioning
confidence: 99%